Is the United Nations a Locus of International Order Imperiality Maintenance? Reflections from the South West Africa Case and Chagos Archipelago Advisory Opinion - Squeff, Tatiana Cardoso; Carrijo, Augusto; Borges, Murilo (Indonesian Journal of International Law, 2022)
The international legal order, seen through third world lenses, is not only embedded with Europe’s colonial past, but also a regime that assimilates the non-European being, its relations and knowledge. Consequently, the possibility of changing such framework is almost an impossible task, being it constantly rejected by hegemonic powers, that is, by a limited number of nations that have been placed in the center of the world order in the turn of modernity and that have not left. Some may argue, yet, that the United Nations presented the international legal order with a different path, breaking with such an imperial system due to the sovereign equality among nations it pledges. And this is exactly what we aim at verifying with this article. We contend that the United Nations presupposes the maintenance of the status quo between hegemonic and subaltern states to perform its activities, basing this assertion in the analysis of the South West Africa decision, delivered by the International Court of Justice – an organ of the U.N. in the 1960s. Nevertheless, taking into consideration the Court’s recent activities on the Chagos Archipelago Opinion of 2019, we note that it tried to break with such a past in a timid manner, particularly by reaffirming both self- determination and the relevance of the U.N. General Assembly. Despite this, we come to the conclusion that it was not enough, being the Organization still a locus of reproduction of imperiality in the international order.